Pembentukan dan Penampilan Pisang Rejang Hibrid Triploid Hasil Persilangan Pisang Rejang Mixoploid Dengan Pisang Rejang Diploid - Poerba, Yuyu S.; Witjaksono, Witjaksono; Handayani, Tri (Perhimpunan Biologi Indonesia, 2016)
Induction of tetraploid from diploid bananas often producing mixoploid plants.Characters of the mixoploidplant is similar to those of tetraploid plants. In this research mixoploid banana cultivar Rejang was crossed withdiploid Rejang to produce triploid hybrid Rejang. Triploid banana is one of plant breeding target because of itsbest vigor and productivity compared to diploid or tetraploid banana. 570 crosses were conducted withmixoploid Rejang as female parents and diploid Rejang as male parents. Out of 570 crosses, 130 hybrid seedswere produced. However, only 19 seeds (14.61%) contained embryos, and only two embryos were developedinto shoots. The two genotypes of developed embryos were then in-vitro propagated and planted in the field.Results of ploidy identification using Flowcytometer showed that the two genotypes were diploids (31%) andtriploids (69%). The triploid hybrid Rejang had plant growth habit of drooping, few suckers, higher and biggerpseudostem, higher bunch weight and fruit weight compared to those of the two parents. The triploid hybridhad similar genetic properties with genetic identity of 0.9174-0.9703.Keywords: Banana, crosses, diploid, Rejang, mixoploid, triploid, hybrids